THE DEVELOPMENT OF MATHEMATICAL PROBLEM SOLVING MODEL WITH CONFLICT COGNITIVE STRATEGY FOR ENHANCING ANALYTICAL DECISION MAKING ABILITIES - Mirawati, Baiq; Asy'ari, Muhammad; Sukarma, I Ketut; Dharmawibawa, Iwan Doddy (Jurnal Pengajaran MIPA, 2019)
This study aims to develop a model of Mathematical Problem Solving with Conflict Cognitive Strategies to facilitate students’ analytical decision making ability. This research is a development research that will produce a model of learning i.e. the model of Mathematical Problem Solving with Conflict Cognitive Strategies along with its devices that valid, practical, and effective to facilitate students’ analytical decision making ability. The results show that the model and supporting devices developed stated: (1) valid (3.0 V£ 4.0); (2) practical (score 3.75 with reliability 98.44%); and (3) effective (n-gain = 0.59; p 0.05) to facilitate students’ analytical decision making ability. Based on these results it can be concluded that the models of Mathematical Problem Solving with Conflict Cognitive Strategy and its supporting device is declared valid, practical, and effective to facilitate students’ analytical decision making ability. AbstrakPenelitian ini bertujuan untuk mengembangkan model Mathematical Problem Solving dengan Strategi Konflik Kognitif untuk melatihkan kemampuan analytical decision making mahasiswa. Penelitian ini merupakan penelitian pengembangan yang akan menghasilkan produk model pembelajaran yaitu model Mathematical Problem Solving dengan Strategi Konflik Kognitif dan perangkat yang valid, praktis dan efektif untuk melatihkan kemampuan analytical decision making mahasiswa. Hasil yang penelitian menunjukkan bahwa model pembelajaran dan perangkat pendukung yang dikembangkan dinyatakan: (1) valid baik secara isi maupun konstruk (3,0 V£ 4,0); (2) praktis (skor 3.75 dengan reliabilitas 98.44%); dan (3) efektif (n-gain= 0.59; p 0.05) untuk melatih kemampuan analitycal decision making mahasiswa. Berdasarkan hasil tersebut dapat disimpulkan bahwa model Mathematical Problem Solving dengan Strategi Konflik Kognitif beserta perangkat pendukung model dinyatakan valid, praktis, dan efektif untuk melatihkan kemampuan analytical decision making mahasiswa. Key words: validity, practicality, effectiveness, model of mathematical problem solving with conflict cognitive strategies, analytical decision making.